Diversity of Threatened Plants and Conservation Efforts in Great Himalayan National Park, Himachal Pradesh, Western Himalaya - Kumar, Ambrish; Kant, Rajni; Dogra, Kuldip Singh; Sekar, K. Chandra; Kharkwal, Kapil; Dash, Sudhanshu Shekhar (Indian Forester, 2022)
The present paper provides scientific information about some valuable threatened plants of economic importance as per the CAMP, 2003/IUCN, 2021 status found in Great Himalayan National Park, Kullu, Himachal Pradesh, a â€œUNESCOâ€ declared World heritage site of Western Himalaya. A total number of 37 plant species belonging to 28 genera under 24 families, that are medicinally important have been recorded and documented in different threat categories as per CAMP, 2003 and IUCN, 2021 status. The study strongly recommends the conservation of these valuable medicinally important threatened plants from the region and encourages their cultivation. An updated list (Table 1) with current nomenclature and current threat status of these species along with some photos (Plate 1) is provided.